Facilities: buildings and equipment - Beernaert, Hedwig (Henry Stewart Talks, 2012)
Facilities, GLP studies in laboratories, greenhouses and in the field, Suitability of location, capacity and design to minimize risk of cross-contamination, Monitoring and registration of environmental conditions, Maintenance, calibration and validation of apparatus, Master validation plan, Histopathology equipment